Measuring SARS‐CoV‐2 aerosolization in rooms of hospitalized patients. Issue 4 (11th July 2022) - Yan, Kenneth; Lin, Jing; Albaugh, Shaley; Yang, Meredith; Wang, Esther; Cyberski, Thomas; Abasiyanik, Mustafa Fatih; Wroblewski, Kristen E.; O'Connor, Michael; Klock, Allan; Tung, Avery; Shahul, Sajid; et al.
Abstract: Objective: Airborne spread of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) remains a significant risk for healthcare workers. Understanding transmission of SARS‐CoV‐2 in the hospital could help minimize nosocomial infection. The objective of this pilot study was to measure aerosolization of SARS‐CoV‐2 in the hospital rooms of COVID‐19 patients. Methods: Two air samplers (Inspirotec) were placed 1 and 4 m away from adults with SARS‐CoV‐2 infection hospitalized at an urban, academic tertiary care center from June to October 2020. Airborne SARS‐CoV‐2 concentration was measured by quantitative reverse transcription polymerase chain reaction and analyzed by clinical parameters and patient demographics. Results: Thirteen patients with COVID‐19 (eight females [61.5%], median age: 57 years old, range 25–82) presented with shortness of breath (100%), cough (38.5%) and fever (15.4%). Respiratory therapy during air sampling varied: mechanical ventilation via endotracheal tube ( n  = 3), high flow nasal cannula ( n  = 4), nasal cannula ( n  = 4), respiratory helmet ( n  = 1), and room air ( n  = 1). SARS‐CoV‐2 RNA was identified in rooms of three out of three intubated patients compared with one out of 10 of the non‐intubated patients ( p  = .014). Airborne SARS‐CoV‐2 tended to decrease with distance (1 vs. 4 m) in rooms of intubated patients. Conclusions: Hospital rooms of intubated patients had higher levels of aerosolized SARS‐CoV‐2, consistent with increased aerosolization of virus in patients with severe disease or treatment with positive pressure ventilation through an endotracheal tube. While preliminary, these data have safety implications for health care workers and design of protective measures in the hospital. Level of Evidence: 2 Abstract : We measured aerosolized SARS‐CoV‐2 in air in the rooms of hospitalized COVID‐19 patients. Viral genetic material was detected in rooms containing intubated patients, and higher viral loads were detected 1m from the upper airway of intubated patients compared with 4m away. These findings suggest that severe COVID‐19 or treatment with mechanical ventilation through an endotracheal tube results in increased SARS‐CoV‐2 aerosolization in the hospital, which has implications for risk to health care workers.